(untitled) (Journal of Innovation in Academia, 2025)
This study aims to construct a conceptual framework for analyzing and forecasting the factors that influence employee turnover intentions in cooperative organizations in Surkhet, Nepal. The study employed a cross-sectional design, with data collected in a single contact with the respondents. The study’s demographic consisted of all cooperative employees in Surkhet, and a convenience sampling method was used to gather 167 responses. Data analysis was conducted using SPSS and AMOS 23 software, with structural equation modeling as the statistical tool for hypothesis testing. Hypotheses were formulated using a deductive research approach. The results indicate that co-worker relations and the working environment were significantly associated with employee turnover intentions among cooperative employees. However, promotions showed no significant association with turnover intentions. This study has certain limitations, including the use of cross-sectional data, self-reports, variations in employee education levels, the comprehension of content, and a relatively small sample size.